1814 Mass. Acts 464 - (:unkn) unknown (My University, 1814)
An Act in Addition to an Act, entitled "An Act to Provide for the Proof of Fire Arms, Manufactured within this Commonwealth," ch. 192, § 2: Requiring all musket barrels and pistol barrels, manufactured within this Commonwealth to be proved by the person appointed according to the provisions of an act . . . with a charge of powder equal in weight to the ball which fits the bore of the barrel to be proved.
Keywords: MANUFACTURE ONLY